2006
DOI: 10.1007/s10350-006-0547-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary Resection With Anastomosis vs . Hartmann's Procedure in Nonelective Surgery for Acute Colonic Diverticulitis: A Systematic Review

Abstract: Patients selected for primary resection and anastomosis have a lower mortality than those treated by Hartmann's procedure in the emergency setting and comparable mortality under conditions of generalized peritonitis (Hinchey > 2). The retrospective nature of the included studies allows for a considerable degree of selection bias that limits robust and clinically sound conclusions. This analysis highlights the need for high-quality randomized trials comparing the two techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
1
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(126 citation statements)
references
References 39 publications
5
107
1
10
Order By: Relevance
“…Two prematurely interrupted RCTs [163,164] and several studies with weaker methodology [165,166] have demonstrated similar mortality and morbidity after resection with primary anastomosis and non-restorative procedures: it seems highly unlikely that an exhaustive RCT will be performed [167].…”
Section: What Are the Treatment Options For Purulent Peritonitis?mentioning
confidence: 99%
“…Two prematurely interrupted RCTs [163,164] and several studies with weaker methodology [165,166] have demonstrated similar mortality and morbidity after resection with primary anastomosis and non-restorative procedures: it seems highly unlikely that an exhaustive RCT will be performed [167].…”
Section: What Are the Treatment Options For Purulent Peritonitis?mentioning
confidence: 99%
“…However, none of these studies were randomized and therefore suffer from a high likelihood of selection bias, with fitter, more stable patients being more likely to be selected for primary anastomosis. A comprehensive systematic review and meta-analysis including 963 patients from 15 studies concluded that mortality after primary anastomosis was significantly lower than after Hartmann's procedure in emergency surgery for acute diverticulitis, with comparable mortality rates for grade Hinchey III and IV generalized peritonitis [42]. However, the authors acknowledge the limitations of the conclusions due to considerable selection bias.…”
Section: Primary Anastomosis Versus Hartmann's Proceduresmentioning
confidence: 94%
“…2,3,7,11,16 Flestar rannsóknir um rof á ristli fjalla um afmarkaðan hluta sjúklinga, ýmist þá sem hafa sömu undirliggjandi orsök eða hafa fengið sömu meðferð. 3,4,6,15,17 Höfundum er ekki kunnugt um að allir sjúk-lingar með rof á ristli, óháð orsökum og meðferð, hafi áður verið skoðaðir saman og það á landsvísu.…”
Section: Inngangurunclassified